Pilot Randomized Controlled Trial of an Exercise Program Requiring Minimal In-person Visits for Youth With Persistent Sport-Related Concussion - Chrisman, Sara P. D.; Whitlock, Kathryn B.; Mendoza, Jason A.; Burton, Monique S.; Somers, Ellie; Hsu, Albert; Fay, Lauren; Palermo, Tonya M.; Rivara, Frederick P. (Frontiers in Neurology, 2019)
Objective: To evaluate feasibility and acceptability of a sub-threshold exercise program with minimal in-person visits to treat youth with persistent sport-related concussion, and explore efficacy for improving concussive symptoms, health-related quality of life, and fear-avoidance. Study design: We conducted a pilot randomized controlled trial comparing a 6 week sub-threshold exercise program requiring only two in-person visits to active control (stretching) for 12–18 year old youth with persistent sport-related concussion. We measured moderate-to-vigorous physical activity pre- and post-intervention using accelerometry, and increased goals weekly via phone contact. We examined feasibility and acceptability using qualitative interviews. We used exponential regression to model differences in trajectory of concussive symptoms by experimental group, and linear regression to model differences in trajectory of health-related quality of life and fear-avoidance of pain by experimental group. Results: Thirty-two subjects randomized, 30 completed the study (n = 11 control, n = 19 intervention), 57% female. Youth and parents reported enjoying participating in the study and appreciated the structure and support, as well as the minimal in-person visits. Exponential regression modeling indicated that concussive symptoms declined more rapidly in intervention youth than control (p = 0.02). Health-related quality of life and fear-avoidance of pain improved over time, but were not significantly different by group. Conclusions: This study indicates feasibility and potential benefit of a 6 week subthreshold exercise program with minimal in-person visits for youth with persistent concussion. Potential factors that may play a role in improvement such as fear-avoidance deserve further study.